Toplotna obdelava aluminijeve zlitine AlCuMgPb (AA2030) med indirektnim iztiskovanjem - Smolej, Anton (Kovine zlitine tehnologije, 1998)
The solution heat treatment and quenching of aluminium alloys during the extrusion is known as "press quenching". Press quenching of high-strength aluminium alloys at indirect press is less known in industrial practice. The paper deals with the possibility of using partial heat treatment of free-cutting AlCuMgPb (AA2030, ISO: AlCu4PbMg) alloy during the indirect extrusion. The laboratory investigations showed that relatively very short solution annealing times are necessary for obtaining sufficiently high strength properties of this alloy after the aging. The extruded and press quenched rods have got higher strength properties in comparison to the standard separate heat treated one. The main reason for these differences is the microstructure. Various heat treatments influence also the machinability of semiproducts. The process of press quenching needs higher working temperatures and extrusion rates what is for this alloy type very difficult to ensure because of the surface tearing. This problem was solved by introducing die cooling with liquid nitrogen which also improved the efficiency of the press and the surface quality of extruded pieces.
Keywords: zlitine aluminija; obdelave toplotne; iztiskovanje indirektno; žarjenje topilno; obdelovalnost; odrezavanje; toplotna obdelava; aluminijeve zlitine; aluminium alloy; aluminum; aluminij; baker; magnezij; svinec